Effectiveness of Mixed Reality in Oral Surgery Training: A Systematic Review - Ruza Bjelovucic; Jan Wolff; Sven Erik Nørholt; Ruben Pauwels; Pankaj Taneja (Sensors, 2025)
Background: Advancements in virtual reality (VR) and augmented reality (AR) technologies have the potential to revolutionize surgical training in oral (OS) and maxillofacial surgery (OMFS). This review aims to discuss the current state of VR and AR applications in surgical training, as well as their impact on education and skills acquisition. Methods: Main search terms used in combination: student, education, training, VR, AR, OS, OMFS, oral surgeon, and maxillofacial surgeon. A comprehensive literature search was conducted from 2012 to 2023 using databases including Cochrane Library, Medline, PubMed, Scopus, Embase, Web of Science, and Google Scholar. Results: Out of 545 potential studies, 12 met the inclusion criteria. The review found that VR applications are predominantly used in surgical training, while AR is notably scarce in this context. Conclusions: While VR cannot replace traditional training methods, its integration into surgical education programs could supplement practical experience on phantoms and real patients.